Аналіз зарубіжного досвіду регулювання творчої активності персоналу вищих навчальних закладів - Тугай, А. М.; Гойко, А. Ф.; Єлішевич, М. А.; Криштоф, С. Д. (Ways to Improve Construction Efficiency, 2012)
Considered foreign experience in regulating creativity staff in higher education institutions.